Implications of the revised EIA Directive. [Themenheft]. - (:unkn) unknown (UVP-Gesellschaft, 2016)
Die Themen im Einzelnen: L. Kornov / U. Kjellerup: Observations and reflections upon the Danish transposition of the EIA Directive: Focus on quality and competence enhancement (S. 130-132); Transposing the revised EIA Directive in France: an opportunity for a genuine systemic approach or just more formalities? (S. 133-142); A. Jiricka / M. Bösch / S. Völler: Learning from the past and upcoming challenges - the implementation of the amendment of the EIA Directive in Austria (S. 143-151); L. Neimane: The revised EIA Directive - the case of Latvia (S. 152-158).
Keywords: Umweltschutz; Naturschutz; Planung; Umweltverträglichkeitsprüfung; Europarecht; Richtlinie; Neuordnung; Biologische Vielfalt; Biodiversität; Strategische Umweltprüfung; Umsetzung; Ländervergleich